Syntactic and structural pattern recognition - NATO Advanced Research Workshop on Syntactic and Structural Pattern Recognition (1986 : Barcelona, Spain and Sitges, Spain); Ferrate, Gabriel A.; North Atlantic Treaty Organization (Berlin : Springer-Verlag, 1988)
Includes bibliographies.